2005
DOI: 10.1074/jbc.m505804200
|View full text |Cite
|
Sign up to set email alerts
|

Death-associated Protein Kinase Is Activated by Dephosphorylation in Response to Cerebral Ischemia

Abstract: Death-associated protein kinase (DAPK) is a calcium calmodulin-regulated serine/threonine protein kinase involved in ischemic neuronal death. In situ hybridization experiments show that DAPK mRNA expression is up-regulated in brain following a global ischemic insult and down-regulated in ischemic tissues after focal ischemia. DAPK is inactive in normal brain tissues, where it is found in its phosphorylated state and becomes rapidly and persistently dephosphorylated and activated in response to ischemia in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 37 publications
6
113
1
Order By: Relevance
“…Although these findings support the notion that calcium/calmodulin-regulated pathways affect the molecular mechanisms that influence synaptic plasticity (47,48), clearly, much remains to be done as a follow up to the novel finding reported here that DAPK is capable of regulating protein synthesis with a possible role in neuronal function. Regardless, the key findings reported here and previously (2,5,8) provide an emerging view of DAPK as a kinase potentially capable of selective modulation of neuronal homeostasis in rapid response to diverse stimuli, with apoptosis as one possible outcome that can be attenuated by targeted therapeutics in disease-relevant events.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Although these findings support the notion that calcium/calmodulin-regulated pathways affect the molecular mechanisms that influence synaptic plasticity (47,48), clearly, much remains to be done as a follow up to the novel finding reported here that DAPK is capable of regulating protein synthesis with a possible role in neuronal function. Regardless, the key findings reported here and previously (2,5,8) provide an emerging view of DAPK as a kinase potentially capable of selective modulation of neuronal homeostasis in rapid response to diverse stimuli, with apoptosis as one possible outcome that can be attenuated by targeted therapeutics in disease-relevant events.…”
Section: Discussionmentioning
confidence: 56%
“…Therapeutic intervention with bioavailable DAPK inhibitors in clinically relevant time windows is neuroprotective in animal models, validating DAPK as a potential drug discovery target for acute and chronic brain injuries (2,4,5). DAPK is highly expressed in the hippocampus, a part of the brain that is essential for memory formation.…”
mentioning
confidence: 99%
“…As all of these findings point out a possible role of DAP-kinase in neurodegenerative disorders and ischemic neuronal injury, DAPkinase is now considered as an attractive target for treatment of CNS injury and degenerative diseases. An aminopyridazine-based selective inhibitor of DAP-kinase has been developed recently and this small molecule displays neuroprotective effect in both hypoxia-and ischemia-induced brain injury models [37,38]. In addition to being involved in the pathological death conditions in neurons, recent study also suggests a function of DAP-kinase in developmentally regulated neuronal cell death.…”
Section: Dap-kinase In Cell Deathmentioning
confidence: 98%
“…A number of studies revealed that DAP-kinase not only mediates neuronal death triggered by various death stimuli and pathological conditions, but also is upregulated at the activity or expression level in response to such death stimuli. For instance, DAPkinase has been shown to play a role in neuronal cell death induced by C2-, C6-, and C8-ceramides [34,35], seizure [36], and various ischemia conditions [37,38]. In vivo, retinal ganglion cells for DAP-kinase null mice displays increased survival following the treatment of cytotoxic level of glutamate [33].…”
Section: Dap-kinase In Cell Deathmentioning
confidence: 99%
“…DAPK is inactive in normal brain tissues, where it is found in its phosphorylated state and becomes rapidly and persistently dephosphorylated and activated in response to ischemia in vivo (Shamloo et al, 2005). …”
Section: Brain Disorders: Ischemiamentioning
confidence: 99%